PENGARUH PENDEKATAN CRT (CULTURALLY RESPONSIVE TEACHING) TERHADAP HASIL BELAJAR SOFTBALL SISWA SMA 8 SEMARANG - Shaputra, Handryca Taufik; Fahmi, Donny Anhar (YLPK Mahardhika, 2025)
The purpose of this research is to determine how the implementation of the culturally responsive teaching (CRT) approach affects the softball learning outcomes of students at SMA 8 Semarang. This research was conducted using a pretest-posttest design with an experimental group. Data were collected through cognitive and psychomotor tests. Data analysis shows that, compared to the pretest results which had an average score of 77,50, the posttest results had a better average score of 90,80. The learning outcomes of students taught using the CRT method have significantly improved, as seen from the analysis results which show an increase of 13,03. This indicates that the CRT approach, which takes into account the cultural background of the students, is effective in improving their softball learning outcomes.